Regulating the near-infrared region to visible-light emission by adjusting cuprophilic interactions for blue light-excited phosphors. Issue 27 (21st June 2021) - Liu, Guang-Ning; Xu, Rang-Dong; Guo, Jin-Shuang; Miao, Jin-Ling; Zhang, Ming-Jian; Li, Cuncheng
Abstract : Reported here for the first time the luminescence regulation of hexanuclear copper(i ) nanoclusters by regulating cuprophilic interactions for blue light-excited phosphors. Abstract : Luminescent copper(i )-based clusters have attracted intensive attention in solid-state lighting. However, rationally regulating the luminescence performance through accurate structural control remains a challenge. Herein, three structurally different hexanuclear copper(i ) nanoclusters were designed by regulating organic ligands to disclose the structure–photoluminescence relationship. The emission bands of the copper(i ) nanoclusters displayed stepwise blueshifts from the near-infrared region to visible red-light region, which could be ascribed to the cluster-centered phosphorescence emission. This is the first study to report the luminescence regulation of hexanuclear copper(i ) nanoclusters by regulating cuprophilic interactions. The underlying mechanism was clearly revealed by precise structural analysis, steady-state, transient, and temperature-dependent luminescence measurements, and theoretical calculations. Importantly, Cu6 (BPT)6 (BPT = 5-bromopyridine-2-thiolate, UJN-Cu4 ) and Cu6 (TPT)6 (TPT = 5-(trifluoromethyl)pyridine-2-thiolate, UJN-Cu5 ) could be effectively excited by a blue light, thereby meeting the requirement for device applications that are based on a commercial 460 nm-blue light-emitting diode (LED) chip. White LEDs and flexible emissive thin films were fabricated to demonstrate the application potential of polynuclear copper(i ) nanoclusters.